Reinforced concrete design of tall buildings - Taranath, Bungale S. (Boca Raton, Florida : CRC Press, 2010)
An exploration of the world of concrete as it applies to the construction of buildings, Reinforced Concrete Design of Tall Buildings provides a practical perspective on all aspects of reinforced concrete used in the design of structures, with particular focus on tall and ultra-tall buildings. Written by Dr. Bungale S. Taranath, this work explains the fundamental principles and state-of-the-art technologies required to build vertical structures as sound as they are eloquent. Dozens of cases studies of tall buildings throughout the world, many designed by Dr. Taranath, provide in-depth insight on why and how specific structural system choices are made."
Chapter 1 Design Concept -- Chapter 2 Gravity Systems -- Chapter 3 Lateral Load-Resisting Systems -- Chapter 4 Wind Loads -- Chapter 5 Seismic Design -- Chapter 6 Seismic Design Examples and Details -- Chapter 7 Seismic Rehabilitation of Existing Buildings -- Chapter 8 Tall Buildings -- Chapter 9 Special Topics.
Keywords: HOUSE AND HOME